The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/5390219
|View full text |Cite|
|
Sign up to set email alerts
|

Intelligent Noise Reduction Algorithm to Evaluate the Correlation between Human Fat Deposits and Uterine Fibroids under Ultrasound Imaging

Abstract: This study aimed to realize the automatic diagnosis of fatty degeneration of uterine fibroids. In this study, the traditional nonlocal means (NLM) algorithm was improved by changing the Euclidean distance and introducing a cosine function and applied to the ultrasonic imaging intelligent diagnosis of patients with fatty degeneration of uterine fibroids. Then, the noise reduction effect of the improved NLM algorithm was evaluated based on several indicators, such as peak signal-to-noise ratio (PSNR), mean squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Sun et al (2021) [ 24 ] concluded that the bilateral filtering intelligent denoising algorithm can improve the diagnostic value of ultrasound elastography for cervical intraepithelial neoplasia (CIN). Luo et al (2021) [ 25 ] also reached a consistent conclusion and gave certain support to this study. Furthermore, the good development prospect of the AI algorithm in medical image processing is proposed.…”
Section: Discussionsupporting
confidence: 87%
“…Sun et al (2021) [ 24 ] concluded that the bilateral filtering intelligent denoising algorithm can improve the diagnostic value of ultrasound elastography for cervical intraepithelial neoplasia (CIN). Luo et al (2021) [ 25 ] also reached a consistent conclusion and gave certain support to this study. Furthermore, the good development prospect of the AI algorithm in medical image processing is proposed.…”
Section: Discussionsupporting
confidence: 87%
“…Noise Reduction Indexes. The traditional NLM algorithm [15] and Bayes Shrink denoising algorithm [16] are introduced to compare with the proposed ONLM algorithm.…”
Section: Noise Reduction Algorithm Based On Nonlocal Meanmentioning
confidence: 99%
“…e number of samples in this study is small. In the future, more physiological and clinical data are expected to be added to further expand the sample research support [27].…”
Section: Discussionmentioning
confidence: 99%